The Influence of Green Products on Green Repurchase Intention Through Green Advertising - Nyoman Mutiara Pradnyani; I Gede Nandya Oktora P (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Starbucks as a coffee shop retail company implements green products by launching several initiatives to reduce the environmental impact by using tumblrs and straws made of paper as well as carrying out green advertising.to increase public awareness of caring for environmental sustainability. This research aims to analyze the influence of green products on green repurchase intention through green advertising. The number of samples used was 100 people. The research method used is quantitative. The data analysis techniques used in this research are Validity Test, Reliability Test, Classical Assumption Test, Path Analysis, Sobel Test and VAF Test. From the research results it can be seen that green products have a positive and significant effect on repurchase intention, green products have a positive and significant effect on green advertising, green advertising has a positive and significant effect on repurchase intention and green advertising is able to mediate the influence of green products on repurchase intention. The results of this research can contribute to Starbucks Badung Regency by providing environmentally friendly information or logos on each product offered to consumers. In making advertisements, always add environmentally friendly elements, offering environmentally friendly products of good quality.